Lidocaine toxicity in the setting of HeartMate II left ventricular assist device. (9th June 2018) - Tunney, R. K.; Whyte, K.; DeAntonio, H. J.
Summary: What is known and objective: Lidocaine infused at 1‐4 mg/min is an appropriate treatment modality for hemodynamically stable ventricular tachycardia (VT) with normal hepatic function. A case of acute lidocaine toxicity in the setting of left ventricular assist device (LVAD) is reported. Case summary: A 71‐year‐old with a HeartMate II LVAD on chronic mexiletine and normal liver function presented with ventricular tachycardia requiring systemic lidocaine and subsequently developed altered mental status with tremors. A lidocaine level obtained within 24 hours of infusion initiation was 7.9 mcg/mL. What is new and conclusion: This case highlights the potential for marked deviation from published pharmacokinetic parameters for a narrow therapeutic window agent with concurrent LVAD. Abstract : A 71‐year‐old male with normal hepatic function and previous HeartMate II Left Ventricular Assist Device (LVAD) developed acute lidocaine toxicity with dose‐adjusted therapy following presentation for ventricular tachycardia. The rationale for acute toxicity is likely multi‐factorial, owing to alterations in hepatic blood flow and volume of distribution (Vd) in the setting of reduced right ventricular function status post LVAD implantation.